OXYGEN THERAPY MANAGEMENT IN THE TREATMENT OF PATIENTS WITH NEW CORONAVIRUS INFECTION - Михаил Исаакович Ликстанов; Елена Евгеньевна Курпе; Анна Владимировна Ромасюк; Евгения Александровна Каменева; Ирина Сергеевна Сергиенко; Вадим Гельевич Мозес; Кира Борисовна Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина (Медицина в Кузбассе)
The experience of solving the problems of the functioning of engineering systems at the stages of launching and direct operation of a redesigned covid hospital is presented.